Development of Biopolymer Nanocomposites Based on Polysaccharides Obtained from Red Algae Chondracanthus chamissoi Reinforced with Chitin Whiskers and Montmorillonite - Rodriguez, SA (2016)
Polysaccharides from various species of algae have many applications in the food and biomedical industry. The aim of this study was to characterize nanocomposites developed from carrageenan extracted from the red algae Chondracanthus chamissoi and reinforced with montmorillonite and chitin nanowhiskers. The nanocomposites showed improved mechanical properties compared to the biopolymeric matrix. Montmorillonite-reinforced nanocomposites displayed the most favorable properties at 5% of clay concentration; meanwhile, the chitin-nanocomposites showed an improvement in the mechanical properties correlating to the increase in chitin concentration. These results will aid in the development of more environmentally friendly materials.